Educational Program Development for Post-Disciplinary Mechatronics Considering Trends, Evolution, and a Novel Reasoning Model - Horváth, Imre; Ábrahám, György (Innovations in Pedagogy and Technology, 2025)
Due to the intertwining scientific, technological, engineering, economic, and social trends, we need to rethink our mental models in the field of mechatronics. The authors (i) completed a broad literature survey of state of the art in this product paradigm-driven discipline, (ii) identified the trends having the highest influence on its disciplinary formation, (iii) analyzed its evolution as a unique scholarly and professional domain, (iv) overviewed its main features and offerings, and (v) examined the manifestation of post-disciplinary mechatronics. They identified five trends heavily influencing its advancement, and demarcated classical, mechatronics, and post-disciplinary mechatronics as three stages of its evolution. The formation of post-disciplinary mechatronics has jointly been enabled by (i) the need for system-level problem-solving, (ii) the emergence of cognitive design, (iii) the proliferation of artificial intelligence technologies, and (iv) the blending of cognitive, human, social, and environmental knowledge. It makes the traditional (discipline combination) models obsolete and calls for a knowledge synthesis-oriented conceptual model. The proposed conceptual framework supports epistemological reasoning about specific knowledge domains, as well as an operational analysis of their explicit relationships in various branches of post-disciplinary mechatronics. The practical utility of the conceptual framework is demonstrated in the development of post-disciplinary educational programs for assistive homecare robotics, as a case study. The paper also proposes follow-up research to explore further deployment possibilities.